BeauHerbs: the herbal formulations for fantastic effects on beauty - Mohamad Zaini, Nurul Sofwa; Kader, Siti Balkhis (University Community Transformation Centre, Universiti Putra Malaysia, 2017)
The concept of beauty and cosmetics is as ancient as mankind and civilization. Women are obsessed with looking beautiful. Herbal formulations always have attracted considerable attention because of their beneficial and fantastic effects on beauty. BeauHerbs application will be happy to serve you with the natural beauty knowledges, feeds and brilliant tips for the user to apply. The mobile application wil serve the user on the details about the benefits of herbs in beauty. The tips for beauty care based on the herbs in order to satisfy the users.